2009
DOI: 10.1007/s10620-008-0660-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Symptom Response to Pyloric Injection of Botulinum Toxin in a Large Series of Gastroparesis Patients

Abstract: Case series report symptom reductions after pyloric botulinum toxin injection in gastroparesis, but small controlled trials show no benefit. Factors that enhance response to therapy are undefined. A retrospective analysis of 179 gastroparetics undergoing pyloric botulinum toxin injection from 2001 to 2007 assessed responses relating to drug dosing, demographic factors, comorbidities, and gastric function. Overall, there was a decrease in gastroparetic symptoms 1-4 months after pyloric botulinum toxin injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
74
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(84 citation statements)
references
References 26 publications
8
74
1
1
Order By: Relevance
“…3,4 Nonetheless, clinical experience and some studies have shown clinical benefit in some patients with gastroparesis. 5 Surgical management mainly encompasses placement of gastric electric stimulators. 6 However, this is FDA-approved at present only as a humanitarian use device.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Nonetheless, clinical experience and some studies have shown clinical benefit in some patients with gastroparesis. 5 Surgical management mainly encompasses placement of gastric electric stimulators. 6 However, this is FDA-approved at present only as a humanitarian use device.…”
Section: Introductionmentioning
confidence: 99%
“…In a retrospective cohort study of 179 patients, doses of 200 units were beneficial in a significantly greater proportion of patients than doses of 100 units (77% vs 54%, P ϭ .02). 77 In this same study, multivariate analysis showed that female sex, age younger than 50 years, and etiology other than diabetes or surgical vagal nerve manipulation were associated with an improved response to therapy. The reported duration of benefit from pyloric botulinum toxin ranges from 1 to 5 months, and repeated injections may be associated with the return of clinical response in a subset of patients.…”
Section: Motility Disordersmentioning
confidence: 79%
“…Numerous uncontrolled studies have shown symptom reduction in patients with gastroparesis treated with pyloric botulinum toxin injection. [73][74][75][76][77] However, 2 placebo-controlled trials involving a small number of patients (55 total) showed no significant benefit. 76,78 If there are benefits from endoscopic botulinum toxin injection, they may depend on the dose used and patient selection.…”
Section: Motility Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Responses depended on toxin dose; subgroup analyses suggested that individuals most likely to respond to increasing BoTox doses included women, those under 50 years old, patients with non-diabetic, non-postsurgical gastroparesis, and possibly individuals without retained food, long-standing opiate use, or with severely delayed gastric emptying. Eighty-seven patients in this series underwent 307 repeat injections that were performed 1-43 months after initial therapy and the initial injection dose (100-200 units) did not affect the reinjection interval [76]. Large, sham-controlled studies are still needed before Botox injection for gastroparesis can be universally recommended [24].…”
Section: Gastroparesismentioning
confidence: 92%